ANALISIS KINERJA BADAN PENDAPATAN DAERAH PASCA PEMBERHENTIAN TENAGA HONORER TAHUN 2017 KABUPATEN KUANTAN SINGINGI - Wetry Kurnia Sari; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Human resource factor is an important element that is considered by the organization, because human resources with good performance are needed to support the successful implementation of organizational activities. In the absence of human resources with good performance, it will be difficult for an organization to achieve its stated goals The purpose of this study is to determine the performance of Regional Income Agency Post-Dismissal of honorary workers in 2017 Kuantan Singingi Regency and to determine the factors that affect the performance of Regional Income Agency Post-Dismissal of honorary workers in 2017 Kuantan Singingi Regency The location of this study is in the District Revenue Agency Kuantan District Singingi.Data collection techniques of this study are documentation, interviews and observations. Analysis of data used by researchers is a reasoning analysis of the phenomena that will be studied, after the data collected through observation techniques and interviews then analyze the data descriptively. Based on the results of the discussions that have been described on the performance of Regional Income Agency Post-Dismissal of honorary workers in 2017 Kuantan Singingi Regency has not been running with the maximum. Based on the five indices used in this study, it is known that there are still many parts of the work that have not run with the maximum. Although the regional revenue agency of Kuantang Singingi has designed and made programs that are very good, the limited funds and human resources are the obstacles.Keywords: Performance, Honorary employee